Emerging Roles of Hydrogen Sulfide in Inflammatory and Neoplastic Colonic Diseases - Guo, Fang-Fang; Yu, Ta-Chung; Hong, Jie; Fang, Jing-Yuan (Frontiers in Physiology, 2016)
Hydrogen sulfide (H2S) is a toxic gas that has been recognized as an important mediator of many physiological processes, such as neurodegeneration, regulation of inflammation, blood pressure, and metabolism. In the human colon, H2S is produced by both endogenous enzymes and sulfate-reducing bacteria (SRB). H2S is involved in the physiological and pathophysiological conditions of the colon, such as inflammatory bowel disease (IBD) and colorectal cancer (CRC), which makes the pharmacological modulation of H2S production and metabolism a potential chemical target for the treatment of colonic diseases. However, the exact mechanisms and pathways by which H2S-mediates normal physiological function and disease in the colon are not fully understood. Besides, the production and release of H2S are modulated by both endogenous and exogenous factors. This review will discuss the production and storage of H2S, its biological roles and the emerging importance in physiology and pathology of IBD and CRC.